Multi-Party Electronic Payments for Mobile Communications - Peirce, Michael (University of Dublin, Trinity College. Department of Computer Science, 2000)
As mobile communications become increasingly sophisticated and ubiquitous, traditional mobile billing with its implicit trust relationships will no longer be adequate. With a large number of different sized mobile networks, a huge variety of value added service providers and many millions of roaming users, it is desirable to remove any unnecessary trust in order to increase security and provide incontestable charging. Billing allows each party involved in a call to eventually receive a share of the revenue generated. An examination of network billing techniques reveals a number of critical shortcomings and emerging problems. We address these issues by designing a multi-party electronic payment scheme that allows all parties involved in a call to be paid in real-time. The mobile user releases an ongoing stream of low-valued micropayment tokens into the network in exchange for the requested services. Dynamic pricing is supported by the association of a pricing contract with the call which specifies the cost of each leg of the call route. Any user with a mobile device and monetary value can use and pay for network access and services in any mobile network into which they roam. We eliminate the need to authenticate the user or contact a distant home network for billing purposes. Extensions to the basic scheme provide mobile wallet functionality and allow user-to-user payments. In addition solutions are designed to cope with frequent handovers between independent picocells, to aggregate several payment streams into one in the core network, and to inter-work with networks using legacy billing techniques. A detailed survey of micropayment techniques forms part of the design process and a number of new micropayment contributions result from observations made. In order to chose appropriate techniques for payment a performance comparison of micropayment schemes is presented based on benchmark measurements taken for the underlying cryptographic algorithms. The multi-party micropayment protocol is prototyped in a wireless environment where it is used to pay for user traffic from existing Internet applications. The proposed scheme has the potential to revolutionise mobile communications by allowing the emergence of many independent inexpensive high-speed picocell networks and by allowing any network entity to sell value added services. Mobile users will be able to select the most appropriate access network and services wherever they roam, paying all parties for resources as they are provided.
Keywords: Computer Science